Focus Assessed Transthoracic Echocardiography (FATE) to facilitate the diagnosis of low risk Pulmonary Embolism in Emergency Department - Sazwan, RS; Devi, YU; Hashairi, FM; Faizia, WAR Wan (Bangladesh Journal of Medical Science, 2013)
A diagnosis of Pulmonary Embolism (PE) is difficult that may be missed because of non specific clinical presentation. However, early diagnosis is fundamental, since immediate treatment is highly effective. Thus, with the availability of ultrasound machine in Emergency Department (ED) can help Emergency Physician to diagnose PE by using Focus Assessed Transthoracic Echocardiography (FATE) to facilitate the diagnosis of PE in low risk patient before proceed with the gold standard investigation which is CT Pulmonary Angiogram (CTPA). We believed this case was likely to be repeated on some readers' clinical practice and this procedure is an appropriate option to consider in such cases. DOI: http://dx.doi.org/10.3329/bjms.v12i4.16101 Bangladesh Journal of Medical Science Vol. 12 No. 04 October 13 Page 459-461